Hiding in plain sight: The emergence of modern dairy farms in India - Burkitbayeva, Saule; Janssen, Emma; Swinnen, Johan (Emerald Publishing Limited, 2023)
This paper provides one of the first and most detailed accounts of the large modern dairy farms that are emerging in the dairy sector in India. Qualitative interviews are used to understand how these farms differ from their traditional smallholder counterparts and how well integrated they are into the value chains.Snowball sampling was used to identify large farmers. In total, 49 in-depth interviews were conducted with large commercial modern farms in Punjab. A detailed description of the main characteristics of these modern dairy farms is provided. Data from previous studies conducted in Punjab is used to compare the new farms with traditional smallholder farms.The modern dairy farms are much more advanced in their use of technology compared to their traditional counterparts. These large commercial modern farms are very well integrated into the value chains. They often, but not exclusively, sell milk to formal supply chains, sometimes on a contractual basis.Most of the literature on the Indian dairy sector focuses on smallholders. However, understanding and acknowledging the emergence of modern dairy farms is very important in understanding the development of value chains not only in the dairy sector in India, but in domestic food sectors in developing countries in general. This qualitative data analysis is a necessary first step if more large-scale representative information is to be collected in the future.